2019
DOI: 10.1002/ehf2.12478
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mitral regurgitation in patients with heart failure referred to a tertiary heart failure clinic

Abstract: Aims Significant mitral regurgitation (MR) is an important predictor for all-cause mortality and heart failure (HF) hospitalizations independent of left ventricular ejection fraction (LVEF). The aims of this study were to investigate (i) in how many patients referred to a tertiary outpatient HF clinic HF therapy could be optimized, (ii) the effect of optimized treatment on MR severity, and (iii) whether a reduction in MR resulted in improvement of symptoms. Methods and results Forty-seven referred patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Decrease in mitral valve regurgitation has found to be associated with better prognosis and symptom relieve 21,22 . Our study showed that LV remodelling by medical treatment also leads to reduction of mitral valve regurgitation, which is consistent with other reports 21–23 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Decrease in mitral valve regurgitation has found to be associated with better prognosis and symptom relieve 21,22 . Our study showed that LV remodelling by medical treatment also leads to reduction of mitral valve regurgitation, which is consistent with other reports 21–23 …”
Section: Discussionsupporting
confidence: 92%
“…21,22 Our study showed that LV remodelling by medical treatment also leads to reduction of mitral valve regurgitation, which is consistent with other reports. [21][22][23]…”
Section: Left Ventricular Remodellingmentioning
confidence: 99%
“…1,11,16,17 Therefore, HF therapies, particularly those that reduce left ventricular end-diastolic volume or cause reverse remodelling, need to be optimized prior to diagnostic work-up. 1,18,19 The crucial role of medical therapy for patient selection and potential effects on trial results was evident in landmark MitraClip trials 9,10 and should therefore be pursued throughout patient journey. Once patients are considered eligible for mitral valve intervention, the intervention type needs to be selected.…”
mentioning
confidence: 99%